Peran Modal Sosial Dan Kepercayaan Interpersonal Dalam Meningkatkan Kinerja Dosen Melalui Komitmen Organisasi Di Lingkungan Universitas Islam Malang - Anik Yuliani; Khalikussabir Khalikussabir; Muhammad Sirojuddin Amin (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to examine the role of social capital and interpersonal trust in improving lecturer performance through organizational commitment at Universitas Islam Malang. This research employs a quantitative approach using Structural Equation Modelling–Partial Least Squares (SEM-PLS). The sample consisted of 204 lecturers selected through proportional sampling. The results indicate that social capital has a positive and significant effect on organizational commitment and lecturer performance. Interpersonal trust has a positive and significant effect on organizational commitment but does not directly affect lecturer performance. Organizational commitment significantly influences lecturer performance. Furthermore, organizational commitment mediates the relationship between social capital and lecturer performance, as well as the relationship between interpersonal trust and lecturer performance. The model explains 44.8% of the variance in lecturer performance and 34.1% of the variance in organizational commitment. These findings highlight the strategic importance of strengthening social relationships and trust within academic institutions to enhance organizational commitment and improve lecturer performance. Keywords: Social Capital, Interpersonal Trust, Organizational Commitment, Lecturer Performance, SEM-PLS